A modelling and simulation GUI tool for Robustness Diagrams with Loop and Time Controls - Labanan, Honneluv T.; Malinao, Jasmine A. (Tacloban City Division of Natural Sciences and Mathematics, University of the Philippines Tacloban College, 2025)
This study introduces TLDR, the first GUI-based modelling and simulation tool for RDLT's. Prior to this, RDLTs lacked modelling and automation tools that are essential for the efficient representation of systems and verifications of their properties. Creating visual models required the use of diagramming tools that are not fine-tuned to the structural requirements of RDLTs, and performing basic operations (e.g. activity extraction) become increasingly tedious when done by hand especially with large and complex models. TLDR offers a user-friendly interface and a comprehensive set of tools for modelling and simulation, which includes drag-and-dropping of components, editing and translation, import/export, simulated/generated activity extraction, vertex simplification, and analysis of Point of Interests. The Course Life cycle System is identified as a real-world system that is modelled and analyzed using TLDR and serve as a major test model for the functional testing of the tool.
Undergraduate thesis (Bachelor of Science in Computer Science) -- University of the Philippines, Tacloban.
Includes bibliographical references.
Keywords: Software engineering